Perancangan UI/UX Aplikasi Pelayanan Masyarakat di Kantor Kecamatan Muara Sugihan Menggunakan Metode Design Thinking - Chearly Cantika Putri; Ahmad Farisi (Yayasan Literasi Sains Indonesia, 2025)
This study aims to design a user interface (UI/UX) for a public service application in Muara Sugihan District to address the constraints of manual systems and geographic barriers for the community. Using the Design Thinking method, this study identified various pain points such as long physical queues, unclear document requirements, and the lack of an effective file tracking system. As a solution, a prototype application was developed that integrates features for submitting Family Cards, ID cards, permits, complaint services, and a real-time notification system. The test results using the System Usability Scale (SUS) showed a very satisfactory score, where the community group gave an Excellent rating (80.58), while the office staff group gave an Good rating (70.83). In addition, based on the User Experience Questionnaire (UEQ-S), this application was assessed as having pragmatic quality and an overall score above average, although the hedonic quality aspect still requires further development. Overall, this design has proven to be functionally effective in digitizing sub-district administrative services, increasing information transparency for residents, and optimizing the work efficiency of officers in systematically managing files.